Basic Baitul Arqam Training in Developing Moral Values and Al-Islam Kemuhammadiyahan - Rahim, Abdul; Risman, Kadar; Yusnan, Muhammad; Kamsiah, Kamsiah (Lembaga Riset dan Inovasi Masyarakat Madani, 2022)
Baitul Arqam Pemuda Muhammadiyah is the main cadreization activity organized to unite the vision and build an understanding of the values of ideology, system, and movement action for youth in Central Buton. Baitul Arqam activities held by the Regional Leader of Muhammadiyah Buton Central Youth (PDPM Buton Tengah) is in the framework of planting about the ideology of Al-Islam Kemuhammadiyahan, strengthening identity as a youth in Central Buton, increasing commitment and integrity. in developing the potential of youth, and shaping the moral values of superior and Islamic youth. Baitul Arqam participants are the youth of Central Buton numbering 15 people. The methods used in these devotional activities are lectures, demonstrations, simulations, and varied discussions. Assessment of participants' conditions using context, input, process and product (CIPP) models on cognitive, affective, and psychomotor aspects. Based on the results of the analysis, the average score of participants on cognitive aspects was 72.47, affective 74.47 and psychomotor 73.27. Thus, the level of youth understanding of the value of Akhlak and Al Islam and Muhammadiyah is at a good level. This means that the application of Baitul Arqam has an effect on improving the understanding of the values of Akhlak and Al Islam and Kemuhammadiyah for the Central Buton Youth.